Sleep and Emotion Regulation among Filipino College Students - Estacio, Joyce DC.; Dy, Marison Felicidad R.; Albor, Rufo Gil Z. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examined the relationship between sleep quality and quantity and emotion regulation strategies among 281 college students from a college of the University of the Philippines Los Banos. Data were collected through a self-administered questionnaire that included the Pittsburgh Sleep Quality Index (PSQI) and the Emotion Regulation Questionnaire (ERQ). Findings indicated that participants had an average of 7.04 hours of sleep, considered sufficient in quantity, but poor in quality (mean PSQI = 8.20). Most students used cognitive reappraisal more frequently than expressive suppression. Pearson correlation analysis revealed that better sleep quality and quantity were generally associated with increased use of cognitive reappraisal. The findings underscore the need to support students’ sleep health and promote adaptive emotion regulation strategies to enhance overall well-being.